Infrared Imaging System for Analysis of Blood Vessel Structure - Fuksis, R.; Greitans, M.; Nikisins, O.; Pudzs, M. (Elektronika ir Elektrotechnika, 2010)
In this paper we discuss two basic systems for analysis of blood vessels for biometric purposes. The infrared palm images that contain information about blood vessel structure are taken using 7 different near infrared wavelengths. Ten images for each wavelength have been captured and analyzed. Image quality was determined by image processing and evaluation algorithms and after that IR imaging methods are compared by the implementation and the calculated effectiveness index. Ill. 7, bibl. 6, tabl. 1 (in English; abstracts in English, Russian and Lithuanian).